The Role of Delawar Hossain Sayedee in the Qur’an Studies of Bangladesh - Rahman, Mizanur (Dinî araştırmalar, 2022)
Looking at history, Bangladesh has a rich identity in terms of Islamic studies. In this country, where more than ninety percent of the population is Muslim, some Islamic scholars engaged in political activities have been influential in politics. In addition to the pressures of imperialism on the religious field, important figures emerged in the Islamic field as well as in the political field in the spread of the Qur'an and the construction of a Bangladeshi society in this way. Delawar Hossain Sayedee is a leading politician and Islamic scholar who warned Muslims in Bangladesh against this situation and supported them in their struggle. It has been emphasized on this topic, due to the scarcity of academic studies on this personality, who has been traveling all over the country, giving sermons, writing books, and trying to introduce people to the Qur'an and Sunnah directly. In this article, the role of Delawar Hossain Sayedee in the field of Qur'an studies in Bangladesh will be explained and one of his most important works, "Translation of the Holy Qur’an", will be evaluated with some of its prominent features.